Pemeliharaan ulat grayak (Spodoptera litura Fabricius) (Lepidoptera: Noctuidae) menggunakan pakan buatan pada skala laboratorium - Ramadhan Taufika; Siti Sumarmi; Dian Hartatie (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
Spodoptera litura is widely used as a test in a research controlling pests in the laboratory so it needs to be maintained to get uniform test insects in large numbers. Rearing of insects in laboratory can use natural food or artificial diets. The purpose of this study was to know the number and percentage of deaths in each phase, the alleged cause of death in each phase, and know the passed of rearing S. litura in laboratory using artificial diet. Rearing of insects is carried out in the Entomology laboratory, Faculty of Biology, Universitas Gadjah Mada. Artificial diet used is Poitout diet with modification. Data obtained from the results of rearing of S. liturain laboratory are then arranged in the form of life tables at the end of the phase, the alleged cause of death, and the percentage of deaths. The results showed the passed of rearing in laboratory using artificial diet was 74.8%. Larvae death by15.7%, pupae that did not develop into imago by 11.3%, imago death by 4.7%, and eggs that did not passed is 18.2%. Alleged causes of death in all phases add to the contamination of diet by fungi, larvae eaten by other larvae, temperature and the capacity of the rearing chamber that are not compatible with the breeding of insects.